Novel Compound Heterozygous Variants of ETHE1 Causing Ethylmalonic Encephalopathy in a Chinese Patient: A Case Report - Chen, Xiaohong; Han, Lin; Yao, Hui (Frontiers in Genetics, 2020)
Abstract Ethylmalonic encephalopathy (EE) is a very rare autosomal recessive metabolic disorder that primarily affects children. Less than one hundred EE patients have been diagnosed worldwide. The clinical manifestations include chronic diarrhea, petechiae, orthostatic acrocyanosis, psychomotor delay and regression, seizures and hypotonia. The ETHE1 gene has been shown to be associated with EE, and genetic sequencing provides concrete evidence for diagnosis. To date, only 37 variants of ETHE1 have been reported as disease-causing in EE patients. We identified two novel ETHE1 variants, i.e. c.595+1G>T at the canonical splice site and the missense variant c.586G>C (p. D196H), in a 3-year-old Chinese boy with EE. The patient had mild symptoms with only chronic diarrhea. The typical symptoms, including petechiae, acrocyanosis and hypotonia, were all absent. Herein, we report on the clinical, biochemical and genetic findings of our patient and review the phenotypes and genotypes of all patients with EE caused by ETHE1 variants with available information. This study supports the early assessment and diagnosis of EE.